THERMODYNAMIC SIMULATIONS ON THE PRODUCTION METHODS OF POROUS CARBIDE DERIVED CARBON MATERIALS - Demirkan, M. Taha (Begell House Inc, 2022)
Carbide derived carbons (CDCs), made by chlorination of carbides (TiC, SiC, ZrC, Mo2C, or Ti3SiC2) at elevated temperature, have shown superior performance over activated carbons in a variety of applications such as supercapacitors, gas storage, or sorption of biomolecules. Thermodynamic simulation based on the Gibbs free energy minimization principle is a powerful tool in predicting reaction products. Such predictions can save experimental time, decrease the number of experiments, and be used to analyze equilibrium reactions between a variety of carbides and halogens at different temperatures. FactSage is one of the largest software packages with a fully integrated database in chemical thermodynamics and can be used to provide accurate predictions to understand chemical phenomena of the reactions for CDCs. The software uses several databases which were collected by a large number of studies compiled over years. In this study, thermodynamic analysis of reactions between various metal carbides and halogens (Cl-2, I-2, F-2, Br-2) has been performed. Work was also done on hydrothermal reactions, halogenation processes, and thermal etching of carbides due to their importance in terms of carbon production. The objective of this work was to provide information on stability and yield of the reaction products for determining the reaction conditions that would lead to specific materials. The reactions were examined as a function of different parameters such as mole fractions, temperature, and pressure to seek the maximum carbon yield within experimentally possible conditions.
Keywords: thermodynamic simulations; carbide derived carbon (CDC); porous carbon; hydrothermal; decomposition; halogenation; binary carbides; ternary carbides; Gibbs free energy; equilibrium conditions